2018
DOI: 10.1016/j.btre.2018.e00284
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production over a catalyst prepared from biomass-derived waste date pits

Abstract: HighlightsValorization of abundantly available waste date pits biomass.Synthesized carbon catalyst possesses pore size >5 suitable for transesterification.Green carbon catalyst found to be highly efficient and provided a biodiesel yield of 98.2%.Produced biodiesel possessed acceptable fuel properties as per ASTM and EN standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 28 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Al-Muhtaseb et al [44] dealt with the oil extracted from the powder of date palms pits (i.e., the hard seeds growing inside date palms), which was used to synthesize a renewable heterogeneous catalyst named "the green carbon catalyst", which was subsequently modified by an alkaline earth-metal (CaO) oxide. Consequently, the biodiesel process has been optimized featuring a maximum yield of 98.2%.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…Al-Muhtaseb et al [44] dealt with the oil extracted from the powder of date palms pits (i.e., the hard seeds growing inside date palms), which was used to synthesize a renewable heterogeneous catalyst named "the green carbon catalyst", which was subsequently modified by an alkaline earth-metal (CaO) oxide. Consequently, the biodiesel process has been optimized featuring a maximum yield of 98.2%.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…In this section, the optimum biodiesel yield was achieved at the 3% catalyst loading, reaction temperature of 80 °C for 20 mins. It was found that a lower catalyst loading of 3% could lead to a higher biodiesel yield compared to previous similar studies on the effect of catalyst loading on the biodiesel yield [19] , [25] . Besides, the reaction temperature and time were both relatively low in comparison to previous research on transesterification of waste oil for clean fuel production [24] .…”
Section: Resultsmentioning
confidence: 47%
“…The waste biomass residues from date palms has been deployed for biodiesel production as pits provide a unique source for biofuel preparation and energy thus avoiding the utilization of the plant edible parts for biofuel production. [47] Coconut is an elongate and round fruit of white, fibrous and oily meat covered by a hairy, brown and thick shell; its oil has antifungal, antioxidant, and antibacterial properties and can be used for the fabrication of metal NPs. [48][49][50] Plums are annually produced in~11,000,000 tons in the world and have been used as raw precursors for industrial utilization as exemplified by the extraction of oil and polyphenols from plum kernel and pomace.…”
Section: Composite Fruitsmentioning
confidence: 99%
“…The antioxidative activities of this fruit emanates from the flavonoids and total phenolic of palm dates [45] (Figure 10) [46] which serve as reducing and stabilizing agents. The waste biomass residues from date palms has been deployed for biodiesel production as pits provide a unique source for biofuel preparation and energy thus avoiding the utilization of the plant edible parts for biofuel production [47] …”
Section: Type Of Fruits and Their Propertiesmentioning
confidence: 99%